Indonesian Nationalism In The Era Of Society 5.0: Degradation And Its Strengthening Strategy - Sanur, Ilham Samudra (Universitas Pendidikan Indonesia (UPI), 2023)
Knowledge about nationalism is very much needed in the framework of the Indonesian nation's defense and security efforts, especially in the era of society 5.0. This study aims to describe how the history of the development of nationalism in Indonesia, the things that influence the degradation and strategies for strengthening nationalism in Indonesia in the era of society 5.0. Compiled using descriptive method with a qualitative approach. The results of this study describe that the most important historical milestones in the process of nationalism in Indonesia were the birth of Budi Utomo and the implementation of the youth oath on October 28, 1908. The factors that influenced the degradation of Indonesian nationalism in the 5.0 era were divided into two, namely internal factors including (1) the nation's backwardness Indonesia from various aspects of life, (2) Democracy that crosses the boundaries of ethics and manners (3) the emergence of ethnocentrism. External factors include (1) the development of globalization, (2) the influence of liberalism and (3) the loss of love for domestic products. Efforts to strengthen nationalism towards the Indonesian nation that have been pursued in the 5.0 era are in the form of fostering Indonesian nationalism through (1) the educational pathway by implementing an independent learning curriculum that is oriented towards developing the profile of Pancasila students in schools, (2) The role of the family by providing special supervision and comprehensive education to children about the surrounding environment and educate children to be proud of using domestic products (3) the role of the government by holding cultural seminars or exhibitions to maintain the preservation of regional culture.